TREATMENT OF OSTEOARTHROTIS OF THE KNEE : SYSTEMATIC REVIEW - Hardiyansah, M. Yudhi; Yulanda Putra, Yosie; Auliya, Ahsan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Osteoarthritis (OA) of the knee, also referred to as degenerative joint disease of the knee, is usually caused by gradual articular cartilage loss as well as wear and tear. Seniors are more likely to experience it.Aims : This systematic review is to review the effect and efficacy of the therapy of knee osteoarthritis.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, ScienceDirect and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 36.803 articles, whereas the results of our search on SAGEPUB brought up 10.021 articles, our search on SCIENCE DIRECT brought up 51.811 articles. The results of the search conducted for the last year of 2014 yielded a total 22.949 articles for PubMed, 6.322 articles for SAGEPUB and 28.399 articles for SCIENCE DIRECT. In the end, we compiled a total of 8 papers, 2 of which came from PubMed, 2 of which came from SAGEPUB and 4 of which came from SCIENCE DIRECT. We included eight research that met the criteria.Conclusion: In summary, although we discovered that several treatments worked, we were unable to rate the effects since the network as a whole lacked coherence and strong confidence in the treatment comparisons.